2007
DOI: 10.1108/08288660710751344
|View full text |Cite
|
Sign up to set email alerts
|

Economics for true human development – future directions

Abstract: Purpose -The purpose of this paper is to show the limitations and inadequacies of the ''Homo Economicus'' model of human behaviour in terms of promoting human development and to outline directions for economics to promote ''true human development''. Design/methodology/approach -The paper first discusses the concept of ''Homo Economicus'' and the criticisms of this model. It then explains the ladder of human development as propounded by Bhagawan Sri Sathya Sai Baba. The paper compares the ''Homo Economicus'' mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Homo economicus is a person whose primary consideration is only his own "utility function," with no regard for the welfare of others [28], and maximize their own results [2]. Homo economicus try to fulfill their own needs because they consider that society is selfish [8][16] and [29].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Homo economicus is a person whose primary consideration is only his own "utility function," with no regard for the welfare of others [28], and maximize their own results [2]. Homo economicus try to fulfill their own needs because they consider that society is selfish [8][16] and [29].…”
Section: Resultsmentioning
confidence: 99%
“…This is satisfying, but it leaves an inner spiritual void. The social conditions and values of western countries are witness to this situation [28].…”
Section: Conventional Economics Lacks An Ethical Dimensionmentioning
confidence: 99%
“…Economics tends to view people as individualistically selfish in their behavior. Therefore, the value it gives to social life is limited only to the benefits that can be obtained from such transactions for individuals (Sivakumar, 2007).…”
Section: Individualismmentioning
confidence: 99%
“…There have been several calls to broaden the purposes of the economy and the goals of capitalism. Sivakumar (2007) called for an economics which can promote true human development and more attuned to global concerns. The Archbishop of Canterbury ( 2009) observed that there is a need to move away from a model of economics which simply assumes that it is essentially about the mechanics of generating money.…”
Section: Pursuit Of Success Regardless Of Consequencesmentioning
confidence: 99%
“…Bhagawan Sri Sathya Sai Baba (2009) emphasises "do business not with the aim of maximising profit, but with the purpose of serving humanity". Sivakumar (2007) has shown how economics and business can promote true human development. When financial markets are used as a vehicle to serve humanity, investors will realise their true purpose.…”
Section: Loss Of Human Valuesmentioning
confidence: 99%